Assessment of cross-cultural adaptations and patient-reported outcome measures relevant to shoulder disorders in Turkish: A systematic review using the COSMIN methodology - Cagdas Isiklar; Gamze Cagla Sirma; Elif Turgut (PLoS ONE, 2025)
Background There are many shoulder assessment outcome measures in the literature that have been studied for validity and reliability. However, there is no study examining the Turkish-adapted patient outcome measures (PROMs) on the shoulder according to the COnsensus-based Standards for the selection of health Measurement Instruments (COSMIN) checklist. In addition, there is a small number of studies that carry out this examination on the shoulder internationally. Determining the most appropriate questionnaires for clinical use will also be an important guide in patient evaluation by filling the gap in both literature and clinical aspects. Objective Our aim in this study is to identify the valid and reliable Turkish scales used to evaluate shoulder pain and disability, to reveal how compatible these scales are with the aspects of study quality and psychometric quality according to COSMIN criteria list. Methods A systematic search was performed in the following electronic databases: MED-LINE, Web of Science (WOS), EMBASE, SCOPUS, and ULAKBIM were searched from inception to September 2024. Results A total of 2890 articles were found in the databases. Four articles were included additionally without a search. Then, after eliminating the duplicates, 2231 articles were included based on the title and abstract search. 63 articles were included in full-text review. After the full-text review, according to our criteria, 29 articles were included in the systematic review. According to the assessment by the COSMIN checklist, 28 articles received the final classification of “inadequate”. Only 1 article (UCLA-Tr) received the final classification of “adequate”. Conclusion There is a wide range of Turkish PROMs available for the shoulder, with only one fully meeting COSMIN methodology criteria. However, this does not imply that other PROMs lack clinical utility. Future studies should focus on refining PROMs by incorporating MCID and PASS scores and prioritizing their responsiveness to enhance their clinical relevance. Additionally, variations in PROM performance across different patient populations highlight the need for context-specific evaluations to ensure their applicability in diverse clinical settings. Trial registration PROSPERO registration number: CRD42022298425.